Digital Global Collaboration: New Ways to Teach International Reporting. (March 2020) - Whitehead, Sandra; Baines, David; Wall, Melissa
World issues and news organizations' operational realities have become so complicated that journalism professionals realize collaboration is the only solution to quality reporting on global issues. Journalism schools need to train their students in the key elements of global collaboration so they can prepare them to stay relevant and cover as many aspects of global events and their implications as possible. This syndicate discussed these issues and new ways in which journalism schools can teach international reporting.